Genomic profiling of human Leishmania braziliensis lesions identifies transcriptional modules associated with cutaneous immunopathology - Novais, Fernanda Oliveira (2015)
Carvalho Filho, Edgar Marcelino de; Carvalho, Lucas Pedreira de. “Documento produzido em parceria ou por autor vinculado à Fiocruz, mas não consta à informação no documento”.